Evaluation of histopathological results of minor salivary gland biopsies in patients with the diagnosis of Sjögren’s syndrome - Gamze Erkılınç; Atalay Doğru; Yaşar Arslan; Rıza Burak Öz; Nermin Karahan; Mehmet Şahin; İbrahim Metin Çiriş (Archives of Rheumatology, 2022)
Objectives: This study aims to evaluate which of the histomorphological criteria defined in labial salivary gland biopsy are more valuable in diagnosing Sjögren’s syndrome (SS) and to examine its correlation with clinical and laboratory findings. Patients and methods: Between January 2005 and January 2019, a total of 927 patients (104 males, 823 females; mean age: 51 years; range, 19 to 85 years) who underwent minor salivary gland biopsies with the suspicion of SS were retrospectively analyzed. The American College of Rheumatology (ACR)/European League Against Rheumatism (EULAR) 2016 classification criteria were used for the classification of SS. We evaluated salivary gland biopsies histomorphologically for the presence and number of lymphocytic focus, as well as chronicity findings (acinar atrophy, ductal dilatation, fibrosis), the presence of lymphocytic infiltration, distribution, localization, ectopic germinal center, and mast cell count. The presence of accompanying diseases, clinical and laboratory findings including age, sex, the presence of dry eye and mouth, and autoantibodies for discriminating SS were noted. Histomorphologically, salivary gland biopsy which fulfilled the adequacy criteria for glandular tissue were compared with the other criteria used to diagnose SS. Results: Strong chronicity and diffuse lymphocytic infiltration were significantly higher in the SS group compared to the non-SS group (p<0.001). Lymphocytic focus score >1 was significantly higher in the SS group compared to the non-SS group (p<0.001). Strong chronicity, acinar atrophy, andductal dilatation were significantly higher in the SS group compared to the non-SS group (p<0.001). Conclusion: More than one lymphocytic focus is the most valuable finding in diagnosing SS. However, it should be kept in mind that, in cases of SS, ductal dilatation, acinar atrophy, and chronicity may be present without lymphocytic infiltration.